Learning - Coastline Community College; Dallas County Community College District ([S.l.] : Coastline Community College in association with Dallas County Community College District [production company], England : AVS Multimedia [distributor], 1990)
Looks at how classical conditioning and operant conditioning have helped scientists understand animal behaviors
Executive producer, Leslie Purdy Ed. D. ; editor, Judy Reidel
Narrator: Kate Porter
Keywords: Learning, Psychology of; Human behavior; Classical conditioning